Clinical significance of immune checkpoint proteins in HPV-infected cervical cancer. Issue 4 (April 2023) - Zou, Wenxue; Huang, Rui; Li, Peihang; Liu, Xiang; Huang, Qingyu; Yue, Jinbo; Liu, Chao
Abstract: Objective: To investigate T cell immunoreceptor with Ig and ITIM domain (TIGIT), V-domain Ig suppressor of T cell activation (VISTA), and lymphocyte-activation gene-3 (LAG-3) expression in pathological tissue of human papillomavirus (HPV)-infected cervical cancer (CC) patients and their relationship with patient prognosis. Methods: Clinical data of 175 patients with HPV-infected CC were collected retrospectively. Tumor tissue sections were stained immunohistochemically for TIGIT, VISTA, and LAG-3. The Kaplan-Meier method calculated patient survival. Univariate and multivariate Cox proportional hazards models analyzed all potential risk factors for survival. Results: When combined positive score (CPS)= 1 was used as the cut-off value, the Kaplan-Meier survival curve showed that the progression-free survival (PFS) and overall survival (OS) of patients with positive expression of TIGIT and VISTA are shorter (both p < 0.05). Univariate COX regression analysis showed that the positive expression of TIGIT and VISTA are related to patient PFS and OS (both HR>1.0 and p < 0.05). Multivariate COX regression analysis showed that TIGIT-positive patients had shorter OS and VISTA-positive patients had shorter PFS (both HR>1.0 and p < 0.05). There is no significant correlation between LAG-3 expression and PFS or OS. When CPS= 10 was used as the cut-off value, Kaplan-Meier survival curve showed that TIGIT-positive patients had shorter OS ( p = 0.019). Univariate COX regression analysis showed that TIGIT-positive expression was associated with the OS of patients (HR=2.209, CI: 1.118–4.365, p = 0.023). However, multivariate COX regression analysis showed that TIGIT expression was not associated significantly with OS. There was no significant correlation between VISTA and LAG-3 expression and PFS or OS. Conclusion: TIGIT and VISTA are associated closely with HPV-infected CC prognosis and are effective biomarkers.